A high-performance biomass-based hard carbon negative electrode material and preparation method thereof
By using diammonium hydrogen phosphate and N and P elements doping in biomass-based hardcoal anode materials, combined with preoxidation and cross-linking curing and high-temperature carbonization processes, the lack of sodium storage performance of traditional biomass-based hardcoal anode materials is solved. Problem, high capacity and excellent sodium storage performance are achieved.
Patent Information
- Application Number
- CN202410225425.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-02-29
AI Technical Summary
Traditional biomass-based hard carbon anode materials have poor sodium storage performance in sodium ion batteries, including lower actual sodium storage amount and first-effect and poor rate performance, which limits their application in the industrial field.
Diammonium hydrogen phosphate is used as the doping source of cross-linking curing agent and heteroatoms N and P elements, and a high-performance biomass-based hard carbon negative electrode material is prepared through preoxidation cross-linking curing reaction and high-temperature carbonization process.
The sodium storage amount and rate performance of biomass-based hardcoal negative electrode materials are improved, and high capacity and excellent sodium storage performance are achieved, providing a new and simple preparation idea and method for biomass-based hardcoal.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials, and specifically relates to a high-performance biomass-based hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] Sodium-ion batteries have attracted much attention in energy storage applications due to their similar energy storage mechanism to lithium-ion batteries, abundant raw materials, and high safety performance. At present, the negative electrodes used more in sodium-ion batteries are hard carbon and soft carbon. As one of the core components of sodium-ion batteries, the negative electrode material affects the battery's first coulombic efficiency, rate performance, and cycle durability. At present, the most studied negative electrode materials for sodium-ion batteries are carbon-based materials. Compared with the graphite negative electrode in lithium batteries, traditional graphite materials cannot meet the high sodium storage capacity. Currently, the negative electrodes that can be used as sodium-ion batteries include: hard carbon, soft carbon, nanofibers, graphene, and carbon nanotubes.
[0003] Biomass-based hard carbon is favored in the field of negative electrode materials due to its advantages such as low cost, abundant sources, high theoretical sodium storage capacity, and easy preparation. However, its poor sodium storage performance, including low actual sodium storage capacity and initial efficiency, as well as poor rate performance, greatly limits the industrial application of biomass-based hard carbon in sodium ion batteries. Therefore, how to develop a high-capacity biomass-based hard carbon negative electrode material and its preparation method is still a technical problem in this field. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a high-performance biomass-based hard carbon negative electrode material and a preparation method thereof, using diammonium hydrogen phosphate as a cross-linking curing agent and a doping source of heteroatom N and P elements, and obtaining a biomass-based hard carbon negative electrode material through a pre-oxidation cross-linking curing reaction combined with a high-temperature carbonization process, thereby providing a way and method for the preparation of high-capacity biomass-based hard carbon negative electrode materials, and effectively solving the problems of low loading of traditional hard carbon active substances, low packing density, and slow ion transfer kinetics.
[0005] In order to achieve the above object, the present invention provides a method for preparing a high-performance biomass-based hard carbon negative electrode material, comprising the following steps:
[0006] (1) ultrasonically immersing the biomass raw material in a mixed solution of anhydrous ethanol / deionized water for 2-10 hours, then washing with deionized water, drying, and crushing to obtain biomass powder; specifically, the crushing can be mechanical crushing or shearing crushing;
[0007] (2) soaking the biomass powder in a diammonium phosphate solution for 5-12 hours, drying it to obtain diammonium phosphate-impregnated biomass, and then pre-oxidizing it for 2-10 hours, and then washing, drying, and crushing it to obtain a biomass-based hard carbon precursor;
[0008] (3) The biomass-based hard carbon precursor is carbonized at high temperature under an inert atmosphere, and then purified and dried to obtain a biomass-based hard carbon negative electrode material.
[0009] In the present technical scheme, anhydrous ethanol is used for immersion to pre-clean away the wax on the surface of the biomass material, which can improve the hydrophilicity of the material, and can improve the water-based wettability of the subsequent cross-linking agent and activator on the biomass surface, and has good composite properties; diammonium hydrogen phosphate is used as a cross-linking curing agent and a doping source of heteroatoms N and P elements. Through a hydrothermal immersion and drying process, the diammonium hydrogen phosphate can be fully impregnated into the biomass powder structure, and a sufficient preliminary hydrothermal cross-linking reaction occurs with the biomass, thereby improving the carbon yield of the biomass in the high-temperature stage, and at the same time, the co-doping of N and P elements on the surface of the hard carbon material can be effectively achieved, thereby improving the sodium storage capacity and rate performance of the hard carbon negative electrode material; through a pre-oxidation cross-linking curing reaction, the diammonium hydrogen phosphate is washed away, and then a high-temperature carbonization process is performed, which can effectively avoid the diammonium hydrogen phosphate activation pore formation in the high-temperature stage from introducing too many defects into the material, and the obtained biomass-based hard carbon negative electrode material has a high specific capacity and first efficiency, and at the same time exhibits excellent sodium storage performance, providing a new and simple negative electrode material preparation idea and method for biomass-based hard carbon.
[0010] Furthermore, in step (1) of the above technical solution, the mass ratio of anhydrous ethanol to deionized water in the anhydrous ethanol / deionized water mixed solution is 1:1-3:1, and the soaking temperature is 40-80°C; the drying temperature is 60-100°C, and the drying time is 6-24h. In this technical solution, the anhydrous ethanol / deionized water mixed solution is used to soak the biomass raw material, which can, on the one hand, wash away impurities such as mud and sand in the original biomass raw material, and on the other hand, dissolve the wax on the surface of the biomass, thereby improving the hydrophilicity of the biomass raw material.
[0011] Furthermore, in step (1) of the above technical solution, the biomass raw material is any one of kapok fiber, coconut shell, apricot shell, walnut shell, rice husk, and bamboo biomass.
[0012] Furthermore, in step (2) of the above technical solution, the mass ratio of the biomass powder to diammonium hydrogen phosphate is 3:1-1:3; the soaking temperature is 80-120°C; the drying temperature is 80-105°C, and the time is 10-48h. In this technical solution, diammonium hydrogen phosphate hydrothermal soaking and subsequent drying process are adopted, so that diammonium hydrogen phosphate can be fully impregnated into the structure of the biomass powder and undergo a preliminary hydrothermal cross-linking reaction with the biomass, which can improve the carbon yield of the biomass in the high temperature stage, and is also conducive to the doping of P element in the high temperature stage, thereby improving the negative electrode capacity.
[0013] Furthermore, in step (2) of the above technical solution, the temperature of the pre-oxidation treatment is 200-350°C, the heating rate is 2-7°C / min; the drying temperature is 70-120°C, the time is 6-24h; the crushing adopts gas mill crushing or mechanical crushing or fluidized bed mill crushing or ball milling or ultrasonic crushing. In this technical solution, low-temperature pre-oxidation is used to transform the biomass material from the original organic biomass into inorganic carbon material, realizing low-temperature pre-carbonization.
[0014] Furthermore, in step (2) of the above technical solution, during cleaning, 1 mol / L hydrochloric acid is first used for pickling, the pickling temperature is 80-100°C, the pickling time is 1-3h, and finally deionized water is used for repeated cleaning until the pH of the filtrate is 7. In the present technical scheme, after the pre-oxidation treatment, the biomass impregnated with diammonium hydrogen phosphate is cleaned, wherein the acid washing mainly washes away some phosphorus-containing compounds formed by the cross-linking and solidification of diammonium hydrogen phosphate and biomass during the pre-oxidation, so as to avoid the activation and pore formation of diammonium hydrogen phosphate during the high-temperature cracking process, which increases the degree of defects and specific surface area of the biomass-based hard carbon material, and affects the negative electrode capacity, first efficiency and cycle stability. If the diammonium hydrogen phosphate is not removed, a SEI film will be formed during the first discharge process, resulting in electrolyte consumption, reducing the reversibility of the battery capacity, and thus reducing the first efficiency of the material; at the same time, a large number of defects and specific surface area reduce the conductivity of the hard carbon, thereby reducing the charge transfer efficiency of the hard carbon negative electrode, and further reducing the capacity and cycle stability and rate performance of the hard carbon negative electrode; at the same time, the ash content, potassium salt, calcium salt, iron salt, etc. of the hard carbon precursor can also be reduced.
[0015] Furthermore, in step (2) of the above technical solution, the graphite interlayer spacing d of the biomass hard carbon precursor is 002 In the technical solution, by doping with P element at high temperature, the graphite interlayer spacing is increased, thereby improving the negative electrode capacity.
[0016] Furthermore, in step (3) of the above technical solution, the high-temperature carbonization temperature is 1000-1600°C, the heating rate is 2-10°C / min, and the carbonization time is 1-6h.
[0017] Furthermore, in step (3) of the above technical scheme, the purification process includes alkali washing, acid washing and water washing, wherein the concentration of the alkali solution is 2-20wt%, and the alkali soaking temperature is 25-70°C; the acid system is hydrochloric acid, sulfuric acid, nitric acid or a mixed acid of the above acids, with a concentration of 1-5mol / L, the acid washing soaking temperature is 50-100°C, and the acid washing soaking time is 1-4h; and the water washing is repeated washing with deionized water until the pH of the filtrate is 7.
[0018] The present invention also provides a high-performance biomass-based hard carbon negative electrode material prepared by the above preparation method, wherein the carbon yield of the biomass-based hard carbon negative electrode material is 30-45%, N and P element heteroatom doping, and the specific surface area is 5-50m 2 / g, ash content is 0.1-0.5wt%, and tap density is 0.5-0.8g / cm 3 , the specific capacity is 280-320mAh / g, and the first efficiency is 85-92%. The obtained hard carbon negative electrode material has excellent sodium storage performance; the negative electrode material is applied to the negative electrode material of lithium ion batteries, and can also show excellent lithium storage performance.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention adopts anhydrous ethanol immersion to pre-clean away wax on the surface of the biomass material, which can improve the hydrophilicity of the material, and can improve the water-based wettability of the subsequent cross-linking agent and activator on the biomass surface, and has good composite properties; using diammonium hydrogen phosphate as a cross-linking curing agent in the low-temperature pre-oxidation process can effectively achieve the co-doping of N and P elements on the surface of the hard carbon material, and improve the sodium storage capacity and rate performance of the hard carbon negative electrode material; after the pre-oxidation treatment, the biomass soaked in diammonium hydrogen phosphate is acid-washed and water-washed, which can wash away some phosphorus-containing compounds in the diammonium hydrogen phosphate and the biomass during the pre-oxidation cross-linking curing, and avoid the high-temperature cracking process. The diammonium hydrogen phosphate activation pores increase the defect degree and specific surface area of the biomass-based hard carbon material, thereby affecting the negative electrode capacity.
[0021] The preparation method of the present invention is simple, and the obtained hard carbon negative electrode material exhibits excellent sodium storage performance, which provides a new and simple idea and method for preparing negative electrode materials for biomass-based hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a microscopic morphology image (10 μm) of the kapok-based hard carbon negative electrode material prepared in Example 1 of the present invention;
[0024] Figure 2 This is a microscopic morphology image (10 μm) of the coconut shell-based hard carbon negative electrode material prepared in Example 2 of the present invention;
[0025] Figure 3 It is a constant current charge and discharge curve diagram of the coconut shell-based hard carbon negative electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0026] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.
[0027] The above-mentioned technical features of the present invention and the technical features specifically described below (such as implementation cases) can be combined with each other to form a new or preferred technical solution.
[0028] The raw materials involved in the embodiments of the present invention are either existing commercially available products or can be prepared according to existing methods.
[0029] Example 1
[0030] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0031] (1) The kapok fiber raw material was ultrasonically immersed in a 50°C anhydrous ethanol / deionized water mixed solution (mass ratio of 1:1) for 6 hours, and then washed with deionized water, dried (dried at 60°C for 10 hours), and crushed (mechanically shredded) to obtain kapok fiber powder;
[0032] (2) Soaking the kapok fiber powder in a diammonium hydrogen phosphate solution (the mass ratio of kapok fiber to diammonium hydrogen phosphate is 1:1) for 10 hours at a soaking temperature of 90°C. After drying (100°C, 24 hours), the kapok fiber impregnated with diammonium hydrogen phosphate is obtained, and then pre-oxidized for 10 hours. After washing, drying, and crushing (ultrasonic crushing), a kapok-based hard carbon precursor is obtained; wherein, the pre-oxidation temperature is 200°C under air atmosphere, and the heating rate is 3°C / min; washing is carried out by soaking and pickling with 1 mol / L hydrochloric acid, the pickling soaking temperature is 90°C, and the pickling soaking time is 2 hours. Finally, deionized water is used for repeated washing until the pH value of the filtrate is 7; the drying temperature is 100°C, and the drying is carried out for 10 hours.
[0033] (3) The kapok-based hard carbon precursor was subjected to high-temperature carbonization under an inert atmosphere, the carbonization temperature was 1200°C, the heating rate was 2°C / min, and the time was 5 hours, and then purified and dried to obtain a kapok-based hard carbon negative electrode material, wherein the purification process was: pickling with 2 mol / L hydrochloric acid solution, the pickling soaking temperature was 90°C, the pickling soaking time was 4 hours, and then repeatedly washed with deionized water until the pH of the filtrate was 7; the drying temperature was 100°C, and the drying time was 10 hours. The microscopic morphology of the obtained kapok-based hard carbon negative electrode material is shown in FIG. Figure 1 shown.
[0034] Example 2
[0035] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0036] (1) ultrasonically immersing the coconut shell raw material in a 100° C. anhydrous ethanol / deionized water mixed solution (mass ratio of 2:1) for 4 h, then washing with deionized water, drying (drying at 80° C. for 12 h), and crushing (mechanically pulverizing) to obtain coconut shell powder;
[0037] (2) Soaking coconut shell powder in diammonium phosphate solution (the mass ratio of coconut shell powder to diammonium phosphate is 2:1) for 12 hours at a soaking temperature of 100°C. After drying (105°C, 10 hours), coconut shell impregnated with diammonium phosphate is obtained, and then pre-oxidized for 2 hours, and then washed, dried, and crushed (jet mill crushed) to obtain a coconut shell-based hard carbon precursor; wherein, the pre-oxidation temperature is 350°C under air atmosphere, and the heating rate is 7°C / min; washing is carried out by soaking and pickling with 1 mol / L hydrochloric acid, the pickling soaking temperature is 100°C, and the pickling soaking time is 2 hours. Finally, deionized water is used for repeated washing until the pH value of the filtrate is 7; the drying temperature is 100°C, and the drying is carried out for 10 hours.
[0038] (3) The coconut shell-based hard carbon precursor was subjected to high-temperature carbonization under an inert atmosphere, the carbonization temperature was 1200°C, the heating rate was 5°C / min, and the time was 3 hours, and then purified and dried to obtain a coconut shell-based hard carbon negative electrode material, wherein the purification process was: pickling with 3 mol / L hydrochloric acid solution, the pickling soaking temperature was 80°C, the pickling soaking time was 3 hours, and then repeatedly washed with deionized water until the pH of the filtrate was 7; the drying temperature was 100°C, and the drying time was 10 hours. The microscopic morphology of the obtained coconut shell-based hard carbon negative electrode material is shown in FIG. Figure 2 shown.
[0039] Example 3
[0040] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0041] (1) The apricot shell raw material was ultrasonically immersed in an 80°C anhydrous ethanol / deionized water mixed solution (mass ratio of 3:1) for 2 h, and then washed with deionized water, dried (dried at 100°C for 6 h), and crushed (mechanically shredded) to obtain apricot shell powder;
[0042] (2) The apricot shell powder was soaked in a diammonium phosphate solution (the mass ratio of apricot shell powder to diammonium phosphate was 1:2) for 5 h at a soaking temperature of 120 ° C. After drying (80 ° C, 48 h), the apricot shell impregnated with diammonium phosphate was obtained, and then pre-oxidized for 8 h. After washing, drying, and crushing (fluidized bed grinding), an apricot shell-based hard carbon precursor was obtained; wherein, the pre-oxidation temperature was 250 ° C in an air atmosphere, and the heating rate was 5 ° C / min; 1 mol / L hydrochloric acid was used for soaking and pickling, the pickling soaking temperature was 80 ° C, and the pickling soaking time was 3 h. Finally, deionized water was used for repeated washing until the pH of the filtrate was 7; the drying temperature was 100 ° C, and the drying time was 10 h.
[0043] (3) The apricot shell-based hard carbon precursor was subjected to high-temperature carbonization under an inert atmosphere at a carbonization temperature of 1400°C, a heating rate of 10°C / min, and a time of 2 hours, and then purified and dried to obtain an apricot shell-based hard carbon negative electrode material, wherein the purification process is as follows: pickling with 5 mol / L hydrochloric acid solution, the pickling soaking temperature is 50°C, the pickling soaking time is 4 hours, and then repeatedly washed with deionized water until the pH of the filtrate is 7; the drying temperature is 100°C, and the drying time is 10 hours.
[0044] Comparative Example 1
[0045] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0046] (1) washing the kapok fiber raw material with deionized water, drying (drying at 60° C. for 10 h), and crushing (mechanically shearing) to obtain kapok fiber powder;
[0047] (2) Soaking the kapok fiber powder in a diammonium hydrogen phosphate solution (the mass ratio of kapok fiber to diammonium hydrogen phosphate is 1:1) for 10 hours at a soaking temperature of 90°C. After drying (100°C, 24 hours), the kapok fiber impregnated with diammonium hydrogen phosphate is obtained, and then pre-oxidized for 10 hours. After washing, drying, and crushing (ultrasonic crushing), a kapok-based hard carbon precursor is obtained; wherein, the pre-oxidation temperature is 200°C under air atmosphere, and the heating rate is 3°C / min; washing is carried out by soaking and pickling with 1 mol / L hydrochloric acid, the pickling soaking temperature is 90°C, and the pickling soaking time is 2 hours. Finally, deionized water is used for repeated washing until the pH value of the filtrate is 7; the drying temperature is 100°C, and the drying is carried out for 10 hours.
[0048] (3) The kapok-based hard carbon precursor is subjected to high-temperature carbonization under an inert atmosphere at a carbonization temperature of 1200°C, a heating rate of 2°C / min, and a time of 5 hours, and then purified and dried to obtain a kapok-based hard carbon negative electrode material, wherein the purification process is: pickling with a 2 mol / L hydrochloric acid solution, the pickling soaking temperature is 90°C, the pickling soaking time is 4 hours, and then repeatedly washed with deionized water until the pH of the filtrate is 7; the drying temperature is 100°C, and the drying time is 10 hours.
[0049] Comparative Example 2
[0050] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0051] (1) The kapok fiber raw material was ultrasonically immersed in a 50°C anhydrous ethanol / deionized water mixed solution (mass ratio of 1:1) for 6 hours, and then washed with deionized water, dried (dried at 60°C for 10 hours), and crushed (mechanically shredded) to obtain kapok fiber powder;
[0052] (2) Soaking the kapok fiber powder in a diammonium phosphate solution (the mass ratio of kapok fiber to diammonium phosphate is 1:1) for 10 hours at a soaking temperature of 25°C. After natural drying, the kapok fiber impregnated with diammonium phosphate is obtained, and then pre-oxidized for 10 hours. After washing, drying, and crushing (ultrasonic crushing), a kapok-based hard carbon precursor is obtained; wherein, the pre-oxidation temperature is 200°C in an air atmosphere, and the heating rate is 3°C / min; washing is performed by soaking and pickling with 1 mol / L hydrochloric acid, the pickling soaking temperature is 90°C, and the pickling soaking time is 2 hours. Finally, deionized water is used for repeated washing until the pH value of the filtrate is 7; the drying temperature is 100°C, and the drying time is 10 hours.
[0053] (3) The kapok-based hard carbon precursor is subjected to high-temperature carbonization under an inert atmosphere at a carbonization temperature of 1200°C, a heating rate of 2°C / min, and a time of 5 hours, and then purified and dried to obtain a kapok-based hard carbon negative electrode material, wherein the purification process is: pickling with a 2 mol / L hydrochloric acid solution, the pickling soaking temperature is 90°C, the pickling soaking time is 4 hours, and then repeatedly washed with deionized water until the pH of the filtrate is 7; the drying temperature is 100°C, and the drying time is 10 hours.
[0054] Comparative Example 3
[0055] A method for preparing a high-performance biomass-based hard carbon negative electrode material comprises the following steps:
[0056] (1) The kapok fiber raw material was ultrasonically immersed in a 50°C anhydrous ethanol / deionized water mixed solution (mass ratio of 1:1) for 6 hours, and then washed with deionized water, dried (dried at 60°C for 10 hours), and crushed (mechanically shredded) to obtain kapok fiber powder;
[0057] (2) Soaking the kapok fiber powder in a diammonium hydrogen phosphate solution (the mass ratio of kapok fiber to diammonium hydrogen phosphate is 1:1) for 10 hours at a soaking temperature of 90°C, and obtaining diammonium hydrogen phosphate-impregnated kapok fiber after drying (100°C, 24 hours), and then pre-oxidizing it for 10 hours, and then crushing it (ultrasonic crushing) to obtain a kapok-based hard carbon precursor; wherein the pre-oxidation temperature in an air atmosphere is 200°C, and the heating rate is 3°C / min;
[0058] (3) The kapok-based hard carbon precursor is subjected to high-temperature carbonization under an inert atmosphere at a carbonization temperature of 1200°C, a heating rate of 2°C / min, and a time of 5 hours, and then purified and dried to obtain a kapok-based hard carbon negative electrode material, wherein the purification process is: pickling with a 2 mol / L hydrochloric acid solution, the pickling soaking temperature is 90°C, the pickling soaking time is 4 hours, and then repeatedly washed with deionized water until the pH of the filtrate is 7; the drying temperature is 100°C, and the drying time is 10 hours.
[0059] Test example
[0060] The hard carbon negative electrode materials obtained in Examples 1-3 and Comparative Examples 1-3 were used as active materials, and the negative electrode slurry was prepared in a ratio of hard carbon: conductive carbon black: CMC: SBR = 94.6: 1.5: 1.4: 2.4. After coating and drying, the hard carbon negative electrode was obtained, and a sodium metal sheet was used as the counter electrode, 1.0M NaPF6 in diglyme = 100Vol% was used as the electrolyte, and button cells were assembled. The specific capacity and first efficiency of the constant current charge and discharge at 0.1C were tested, and the results are shown in Table 1. The 0.1C constant current charge and discharge curve of the coconut shell-based hard carbon negative electrode material in Example 2 is shown in Table 1. Figure 3 shown.
[0061] Table 1 Specific capacity and initial efficiency
[0062] Group 0.1C constant current charge and discharge mAh / g First effect% Example 1 301 89% Example 2 320 92% Example 3 305 91% Comparative Example 1 290 89% Comparative Example 2 280 89% Comparative Example 3 200 65%
[0063] It can be seen from the data in Table 1 that the biomass-based hard carbon negative electrode material obtained by the preparation method of the present invention has the performance of high capacity and high first efficiency. For example, the specific capacity of Example 2 is as high as 320mAh / g at 0.1C, and the first efficiency is 92%, showing excellent capacity performance. In Comparative Example 1, since the wax on the surface of the biomass was not pre-cleaned with anhydrous ethanol, the hydrophilicity was poor, which affected the subsequent impregnation and cross-linking reaction, thereby affecting the specific capacity at 0.1C constant current charge and discharge; in Comparative Example 2, since the room temperature immersion and natural drying were used, the subsequent biomass cross-linking reaction was affected, thereby affecting the specific capacity at 0.1C constant current charge and discharge; in Comparative Example 3, since the kapok fiber impregnated with diammonium hydrogen phosphate was directly crushed after pre-oxidation, the diammonium hydrogen phosphate was not washed off, and defects were introduced in the subsequent high-temperature stage of diammonium hydrogen phosphate activation and pore formation, which significantly reduced the specific capacity and first efficiency of the negative electrode material.
[0064] In summary, the present invention optimizes the preparation method and adopts anhydrous ethanol immersion to improve the water-based wettability of subsequent cross-linking agents and activators on the biomass surface, and has good composite properties; using diammonium hydrogen phosphate as a cross-linking curing agent in the low-temperature pre-oxidation process can effectively realize the co-doping of N and P elements on the surface of the hard carbon material, and improve the sodium storage capacity and rate performance of the hard carbon negative electrode material; after the pre-oxidation treatment, the biomass impregnated with diammonium hydrogen phosphate is acid-washed and water-washed to wash away phosphorus-containing compounds such as diammonium hydrogen phosphate, and avoid the high-temperature pyrolysis process. The activation and pore formation of diammonium hydrogen phosphate increases the defect degree and specific surface area of the biomass-based hard carbon material, which affects the negative electrode capacity. The obtained biomass-based hard carbon negative electrode material has high capacity and first efficiency and excellent performance; at the same time, the preparation method is simple, and the obtained hard carbon negative electrode material exhibits excellent sodium storage performance, which can provide a new and simple negative electrode material preparation idea and method for biomass-based hard carbon.
[0065] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance biomass-based hard carbon negative electrode material, characterized in that: The following steps are involved: (1) Ultrasonic immersion of the biomass raw material in a mixed solution of anhydrous ethanol / deionized water for 2-10 hours, followed by washing, drying, and crushing with deionized water to obtain biomass powder; (2) Soaking the biomass powder in a diammonium phosphate solution for 5-12 hours, drying at 80-105°C for 10-48 hours to obtain diammonium phosphate-impregnated biomass, and then pre-oxidizing it for 2-10 hours, and then washing, drying, and crushing it to obtain a biomass-based hard carbon precursor; the mass ratio of the biomass powder to diammonium phosphate is 3:1-1:3, and the soaking temperature is 80-120°C; when washing, first use 1 mol / L hydrochloric acid for soaking and pickling, the pickling soaking temperature is 80-100°C, the pickling soaking time is 1-3 hours, and finally use deionized water to repeatedly wash until the pH of the filtrate is 7; (3) The biomass-based hard carbon precursor is carbonized at high temperature under an inert atmosphere, and then purified and dried to obtain a biomass-based hard carbon negative electrode material.
2. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the mass ratio of anhydrous ethanol to deionized water in the anhydrous ethanol / deionized water mixed solution is 1:1-3:1, and the soaking temperature is 40-80°C; the drying temperature is 60-100°C, and the drying time is 6-24h.
3. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (1), the biomass raw material is any one of kapok fiber, coconut shell, apricot shell, walnut shell, rice husk, and bamboo biomass.
4. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (2), the pre-oxidation treatment temperature is 200-350°C, and the heating rate is 2-7°C / min; the drying temperature is 70-120°C, and the time is 6-24h; and the pulverization is performed by gas mill pulverization, mechanical pulverization, fluidized bed mill pulverization, ball milling, or ultrasonic pulverization.
5. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (2), the graphite interlayer spacing d of the biomass-based hard carbon precursor is 002 0.38-0.42 nm.
6. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (3), the high temperature carbonization temperature is 1000-1400°C, the heating rate is 2-10°C / min, and the carbonization time is 1-6h.
7. The method for preparing a high-performance biomass-based hard carbon negative electrode material according to claim 1, characterized in that: In step (3), the purification process includes alkali washing, acid washing and water washing, wherein the concentration of the alkali solution is 2-20wt%, and the alkali soaking temperature is 25-70°C; the acid system is hydrochloric acid, sulfuric acid, nitric acid or a mixture of the above acids, with a concentration of 1-5mol / L, the acid washing soaking temperature is 50-100°C, and the acid washing soaking time is 1-4 h; the water washing is repeated washing with deionized water until the pH of the filtrate is 7.
8. A high-performance biomass-based hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The carbon yield of the biomass-based hard carbon negative electrode material is 30-45%, N and P element heteroatom doping, and the specific surface area is 5-50m 2 / g, ash content is 0.1-0.5 wt%, and tap density is 0.5-0.8 g / cm 3 , the specific capacity is 280-320mAh / g, and the first efficiency is 85-92%.
Citation Information
Patent Citations
Preparation method and use method of biomass carbon fertilizer
CN102515914A